Possibilities of monitoring intraocular pressure using a transpalpebral scleral tonometry in cases of corneal and ocular surface pathology - María Ángeles del Buey; Paula Casas (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2022)
Cornea and ocular surface specialists need a form of tonometry for those cases where it is not possible to use Goldmann applanation tonometry (GAT) on the cornea. There are many situations in which the condition of the cornea prevents adequate monitoring of the intraocular pressure (IOP) with applanation tonometry, such as the existence of neurotrophic ulcers, corneal infections, or abscesses, corneal injuries or corneal de-epithelization. In addition, certain ocular postoperative situations, require a digital estimation of high or low pressure as the only option for IOP monitoring.